Correlation of Chemotherapy Frequency with Nutritional Status and Leukocyte Levels in Breast Cancer Patients at Abdoel Wahab Sjahranie Samarinda Regional General Hospital - Pirda Wulandari; Joko Sapto Pramono; Sepsina Reski (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the relationship between chemotherapy frequency and nutritional status and leukocyte levels in breast cancer patients. This research is an analytical observational study with a cross sectional research design. This research was conducted in September 2023. The sample consisted of 33 people and was taken using accidental sampling technique. There are 2 types of research data, namely primary data (frequency of chemotherapy and nutritional status) and secondary data (leukocyte levels). Data analysis used the Pearson chi-square test (α<0.050) with the Pearson product moment test. The results of the study showed that there was a relationship between the frequency of chemotherapy and the nutritional status of breast cancer patients (p=0.043) with a low correlation (r=-0.235) and there was a relationship between the frequency of chemotherapy and the leukocyte levels of breast cancer patients (p=0.009) with a medium correlation. or quite strong (r=-0.530).